2015
DOI: 10.1103/physreva.91.061403
|View full text |Cite
|
Sign up to set email alerts
|

Dressing effects in the attosecond transient absorption spectra of doubly excited states in helium

Abstract: Strong-field manipulation of autoionizing states is a crucial aspect of electronic quantum control. Recent measurements of the attosecond transient absorption spectrum (ATAS) of helium dressed by a few-cycle visible pulse [C. Ott et al., Nature (London) 516, 374 (2014)] provide evidence of the inversion of Fano profiles. With the support of accurate ab initio calculations that reproduce the results of the latter experiment, here we investigate the new physics that arise from ATAS when the laser intensity is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…In Fig. 1c it is not possible to discern the characteristic hyperbolic fringes associated to the free-induction decay expected for isolated states [44,52,53]. However, all peaks do appear to be broader at negative time delays, when the SWIR follows the X-ray pulse.…”
mentioning
confidence: 90%
“…In Fig. 1c it is not possible to discern the characteristic hyperbolic fringes associated to the free-induction decay expected for isolated states [44,52,53]. However, all peaks do appear to be broader at negative time delays, when the SWIR follows the X-ray pulse.…”
mentioning
confidence: 90%
“…During last decade, autoionizing states of argon [28] and helium [29][30][31][32][33][34][35][36][37] were reinvestigated experimentally by the pumpprobe scheme and theoretically by implying sophisticated models [38,39] and numerical solution of the time-dependent Schrödinger equation [40]. In almost all studies mentioned above, a control over the Fano-interference has been achieved by an interplay between the intense high-frequency pump and low-frequency probe pulses.…”
Section: Introductionmentioning
confidence: 99%
“…With high-order harmonic generation sources, the resonant excitation and probe of these transitions under the influence of ultrashort NIR lasers became experimentally accessible. The interest has focused particularly on investigating the laser coupling of two-electron dynamics with intense NIR sources [6][7][8][9][10][11]. More recently, a study revealed the temporal build-up of the Fano resonance around an isolated doubly excited state [12].…”
Section: Introductionmentioning
confidence: 99%